Post-depositional disturbance and spatial organization at exposed open-air sites: Examples from the Middle Stone Age of the Makgadikgadi Basin, Botswana - Staurset, S; Coulson, S; Mothulatshipi, S; Sallie, BL; Nash, DJ; Thomas, D (Elsevier, 2022)
The influence of natural factors such as bioturbation or sediment movement caused by wind and water is a perennial concern for Stone Age site selection and subsequent interpretation. This paper discusses the spatial artefact distribution of five recently excavated, open-air exposed Middle Stone Age (MSA) sites in Ntwetwe Pan, Botswana. The finds comprise lithic assemblages dominated by MSA points, manufactured in a variety of silcretes. The sites were examined following the assumption that archaeological sites are the product of a combination of natural and cultural factors, occurring both during and after artefacts are deposited. The results indicate that some of these exposed pan floor sites do preserve cultural artefact distribution patterns, and that the level of post-depositional disturbance varies locally. Refitting was an important tool of analysis, especially on the largest site, MAK33, where it was possible to identify working areas that focussed on different modes of lithic manufacture. In combination with a chaîne opératoire analysis of lithic production stages, it was then possible to map movement of artefacts across the site. We argue that the spatial organization of open-air sites may preserve behavioural records that are not present at caves and rock shelters, and provide a view into the short-term, single-use locations that likely formed the basis of MSA occupation patterns.